Fatigue Analysis of Pipeline End Manifold (PLEM) due to Cyclic Load from Subsea Hoses - Rizal Arif Pratama; Handayanu; Nur Syahroni (International Journal of Marine Engineering Innovation and Research, 2025)
To ensure the continuity of delivering crude oil from the Central Plant to the Floating Storage and Offloading (FSO), PHE ONWJ plans to replace existing pipelines and Pipeline End Manifolds (PLEM) in order to enhance the integrity and reliability of the Marine Terminal facilities. The configuration changes resulting from the installation of new pipelines and PLEM alter the dynamic interactions between the subsea hoses connected to the New PLEM and Old PLEM, leading to different load conditions on the new PLEM structure. Considering the importance of PLEM in crude oil transfer process from wells within the ONWJ working area to the FSO, thus this research will conduct a fatigue analysis of the Pipeline End Manifold (PLEM) due to cyclic tension loads from subsea hoses. The objective of this research is to predict the fatigue life of New PLEM A structure by applying Palmgren-Miner Rule. The study will begin with an analysis of the mooring lines system and subsea hoses connected to the new PLEM to identify the cyclic tension loads acting on the structure. The analysis was performed using time domain simulation with output in the form of a tension time history. The results of the time tension history will then be processed to find the tension range cycle value using the Rainflow cycle counting method. Furthermore, to assess the stress distribution caused by cyclic loads from the subsea hoses, a local stress analysis will be performed using hotspot stress method by finite element analysis (FEA) which refers to DNV-RP-C203. The result of hotspot stress analysis will be used for the fatigue life calculation of the New PLEM A structure. The analysis results show that the lowest fatigue life of the new PLEM A structure occurs at the connection between pipe support and skid, with a fatigue life value of 17.63 years and a damage ratio of 0.0113. In contrast, the connection between the elbow pipe and flange exhibits a significantly higher fatigue life of 499.38 years and a damage ratio of 4 × 10-4